Effect of Soil Types and Fertilizers on Nursery Crop of Dalbergia sissoo Roxb. - Naugraiya, M.N. (Indian Journal of Agroforestry, 2020)
A study conducted on nursery crop of Dalbergia sissoo showed statistical significant results for the initial nodulation and growth behaviour of seedlings in relation to soil (S1 & S2) rhizobial inoculation (T0 & T1) and inorganic fertilizers (F0, F1, F2Â & F3) and the better results were found in red soil (S1), rhizobial inoculation (T1) and application of phosphorus (F2) as solo and their combination (T1 x S1 x F2) Inoculations enhanced the nodulation and it was maximum with phosphorous in both the soil. Overall growth (1O.5 cm shoot and 15.7 cm root length) and dry matter production (62 mg/plant) and nodulation (23 nodule/plant) were found maximum in T1 x S1 X F2 and the minimum in both rhizobium untreated (T0) and treated (T1) plants grown with application of 30N kg/ha, thus presence of nitrogen in soil discouraged the formation of nodules which ultimately reflected in plant growth.